2016
DOI: 10.1038/srep38973
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and anticancer PDMS surface for mammalian cell growth using the Chinese herb extract paeonol(4-methoxy-2-hydroxyacetophenone)

Abstract: Polydimethylsiloxane (PDMS) is widely used as a cell culture platform to produce micro- and nano-technology based microdevices. However, the native PDMS surface is not suitable for cell adhesion and is always subject to bacterial pollution and cancer cell invasion. Coating the PDMS surface with antibacterial or anticancer materials often causes considerable harm to the non-cancer mammalian cells on it. We have developed a method to fabricate a biocompatible PDMS surface which not only promotes non-cancer mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…At present, seven classes of compounds have been isolated from CM: phenols, monoterpenes, monoterpene glycosides, flavonoids, tannins, triterpenoids and others [9] [10] [11] [12]. Phenols and monoterpene glycosides are the predominant active ingredients [13] [14] [15] [16]. Nevertheless, the therapeutic properties of CM always correlate with its sources and geographical origins [17].…”
Section: Introductionmentioning
confidence: 99%
“…At present, seven classes of compounds have been isolated from CM: phenols, monoterpenes, monoterpene glycosides, flavonoids, tannins, triterpenoids and others [9] [10] [11] [12]. Phenols and monoterpene glycosides are the predominant active ingredients [13] [14] [15] [16]. Nevertheless, the therapeutic properties of CM always correlate with its sources and geographical origins [17].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we showed that germacrone inhibits the proliferation and migration of MCF-7 breast cancer cells 5 by the inhibition of ERα signaling 24 . The expressions of the anti-apoptotic Bcl-2 and Bcl-xL protein and the pro-apoptotic TP53 and TP21 were dose-dependently regulated by germacrone as well 25 27 . While the research on curdione and furanodiene are limited, the results from this study provide a good starting point for further studies.…”
Section: Discussionmentioning
confidence: 96%
“…It has been proved that Loquat leaf can inhibit a variety of cocci and bacillus [13] . Paeonol and the like in cortex moutan have anti-inflammatory effect [14] . The combined use of these drugs can relieve inflammation and eliminate skin lesions.…”
Section: Discussionmentioning
confidence: 99%